Upaya Meningkatkan Sosial Emosional Anak Usia 5-6 Tahun melalui Media Film Animasi di TK Haholongan Desa Siundol Julu Kec. Sosopan Kab. Padang Lawas - Hasibuan, Intan Wahyuni; Arlina, Arlina; Pulungan, Enny Nazrah (Asian Journal of Early Childhood and Elementary Education, 2025)
This study aims to understand the role of animated film media in improving the socio-emotional development of children aged 5-6 years at TK Haholongan, Siundol Julu Village, Sosopan District, Padang Lawas Regency, during the 2023-2024 academic year. To collect data, the researcher used the classroom action research method, employing observation, interviews, and pre-tests. The study involved 11 children, consisting of 4 boys and 7 girls. The results indicate that children's socio-emotional development improved following interventions using animated film media. During the pre-test in the pre-cycle, the percentage of socio-emotional development was 36.36% (4 children) categorized as "starting to develop," and 63.63% (7 children) categorized as "not yet developing." In Cycle I, improvement was observed, with 5 children (45.45%) categorized as "developing as expected," while 6 children (54.54%) remained in the "starting to develop" category. In Cycle II, significant progress was noted, with 9 children (81.81%) categorized as "developing very well," and 2 children (18.18%) categorized as "developing as expected." Thus, animated film media can effectively enhance the socio-emotional development of children aged 5-6 years at TK Haholongan, Siundol Julu Village, Sosopan District, Padang Lawas Regency, during the 2023-2024 academic year.